2022
DOI: 10.31635/ccschem.021.202101472
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Regio- and Enantioselective Hydroarylation of 1,3-Dienes with Indoles

Abstract: The regio-and enantioselective functionalization of 1,3-dienes has become a powerful tool for the synthesis of allylic compounds, yet it remains a challenge for aliphatic dienes. Herein, we report a nickel-catalyzed asymmetric hydroarylation reaction of aliphatic and aromatic dienes with indoles to afford chiral indole derivatives. Because the reaction is performed under redox-neutral and mild conditions, various functional groups are tolerated in the reaction. Density functional theory calculations elucidate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Promising levels of enantioselectivity (77–84% ee ) and exquisite 1,2-regioselectivity were obtained using aryl-substituted linear dienes and a chiral spiro amino–phosphine ligand ( L9 ). In a following study, the Zhou laboratory established that nonprotected indoles were competent substrates for the selective hydro­(hetero)­arylation of 1,3-dienes (Figure B) . With the use of a chiral bisphosphine ligand ( L10 or L11 ) and diverse indole derivatives, excellent regio- and enantioselectivity were obtained for both aryl- and alkyl-substituted linear dienes over a range of ca.…”
Section: Nickel-catalyzed Enantioselective Hydrocarbonation Of 13-dienesmentioning
confidence: 99%
“…Promising levels of enantioselectivity (77–84% ee ) and exquisite 1,2-regioselectivity were obtained using aryl-substituted linear dienes and a chiral spiro amino–phosphine ligand ( L9 ). In a following study, the Zhou laboratory established that nonprotected indoles were competent substrates for the selective hydro­(hetero)­arylation of 1,3-dienes (Figure B) . With the use of a chiral bisphosphine ligand ( L10 or L11 ) and diverse indole derivatives, excellent regio- and enantioselectivity were obtained for both aryl- and alkyl-substituted linear dienes over a range of ca.…”
Section: Nickel-catalyzed Enantioselective Hydrocarbonation Of 13-dienesmentioning
confidence: 99%
“…Very recently, Zhou et al also reported that nickel hydride catalysts promoted similar regio- and stereoselective addition of indoles to aliphatic 1,3-dienes. 111…”
Section: Metal Hydride Reaction Manifoldsmentioning
confidence: 99%
“…t BuOK in isopropanol at 60 °C for 72 h (Scheme 38). 59 The regio and enantioselectivity of the hydroarylation reaction was unaffected by the length and steric bulk of the diene's alkyl chain. Various functional groups such as olefins, ether, ester, and halide were also compatible in this reaction.…”
Section: Intermolecular Hydroarylation Reactionsmentioning
confidence: 99%